PENTINGNYA BAHASA INGGRIS UNTUK ANAK USIA DINI DI DESA PURWOASRI, 28 METRO UTARA - Triyanto, Diyan; Astuti, Rahma Yudi (Jurnal Studi Gender dan Anak, 2021)
This paper discusses about the importance of English education for early childhood. English education is needed along with the progress of a country. Therefore, education English as an international language was introduced as early as possible to the students before the age of 12 years. Early childhood is children in the age range 2-7 years and is a golden period for language development. They were able to learn to speak like native speakers. However, they are still on the cognitive development of preoperational that has a high self-centered, do not understand abstract things, just to understand the symbols and still pre-logical thinking. Therefore, English language education for children in need of methods and processes appropriate and effective teaching, for example through song, music and movement. The method is considered successful and very suitable for early childhood in learning English. To develop the method also requires the teacher's role as an educator in the process of learning English.